Multiple Forces Contribute to Cell Sheet Morphogenesis for Dorsal Closure in Drosophila - Kiehart, Daniel P. (The Rockefeller University Press, 2000)

(untitled)
The molecular and cellular bases of cell shape change and movement during morphogenesis and wound healing are of intense interest and are only beginning to be understood. Here, we investigate the forces responsible for morphogenesis during dorsal closure with three approaches. First, we use real-time and time-lapsed laser confocal microscopy to follow actin dynamics and document cell shape changes and tissue movements in living, unperturbed embryos. We label cells with a ubiquitously expressed transgene that encodes GFP fused to an autonomously folding actin binding fragment from fly moesin. Second, we use a biomechanical approach to examine the distribution of stiffness/tension during dorsal closure by following the response of the various tissues to cutting by an ultraviolet laser. We tested our previous model (Young, P.E., A.M. Richman, A.S. Ketchum, and D.P. Kiehart. 1993. Genes Dev. 7:29–41) that the leading edge of the lateral epidermis is a contractile purse-string that provides force for dorsal closure. We show that this structure is under tension and behaves as a supracellular purse-string, however, we provide evidence that it alone cannot account for the forces responsible for dorsal closure. In addition, we show that there is isotropic stiffness/tension in the amnioserosa and anisotropic stiffness/tension in the lateral epidermis. Tension in the amnioserosa may contribute force for dorsal closure, but tension in the lateral epidermis opposes it. Third, we examine the role of various tissues in dorsal closure by repeated ablation of cells in the amnioserosa and the leading edge of the lateral epidermis. Our data provide strong evidence that both tissues appear to contribute to normal dorsal closure in living embryos, but surprisingly, neither is absolutely required for dorsal closure. Finally, we establish that the Drosophila epidermis rapidly and reproducibly heals from both mechanical and ultraviolet laser wounds, even those delivered repeatedly. During healing, actin is rapidly recruited to the margins of the wound and a newly formed, supracellular purse-string contracts during wound healing. This result establishes the Drosophila embryo as an excellent system for the investigation of wound healing. Moreover, our observations demonstrate that wound healing in this insect epidermal system parallel wound healing in vertebrate tissues in situ and vertebrate cells in culture (for review see Kiehart, D.P. 1999. Curr. Biol. 9:R602–R605).